A piecewise negative stiffness mechanism and its application in dynamic vibration absorber. Issue 2 (30th December 2021) - Hao, Yan; Shen, Yongjun; Wang, Junfeng; Yang, Shaopu
Abstract: A new type of piecewise negative stiffness (NS) mechanism is designed and the relationship between the force and displacement is studied. At first, the prototype of the piecewise NS mechanism is established, and the stiffness characteristic of this mechanism is analyzed. Then, the piecewise NS mechanism is applied to dynamic vibration absorber (DVA) system to establish a dynamic model with the piecewise linearity. The differential motion equations are derived according to Newton's law of mechanics. The approximate analytical solution and the amplitude frequency curve of the system with the piecewise NS are obtained by means of the averaging method. The correctness of the analytical solution is proved by comparing with the numerical solution. In the end, the comparisons with two other traditional DVAs show that the system in this paper has better vibration reduction effect under the condition of harmonic excitation and random excitation.